Managerial Competency Pattern Design - Mahdieh Sadat Khoshouei; Hamid Reza Oreyzi; Aboulghasem Nouri; Afshin Jahanbazi (مطالعات مدیریت راهبردی, 2013)
The study purpose to develop managerial competency model in Isfahan Province Gas Company. Semi-structured interviews and Managerial Competencies Questionnaire were conducted with 15 managers selected purposefully (maximum variation sampling) from among the different levels of management in Isfahan Gas Company. Also, Gas monthly magazine (Nedaye Gas), job description of managers, web sites of National Iranian Gas Company and thirty provinces studied. Then concepts were collected and categorized into 8 main categories and 78 sub categories. Finally، reliability and validity of model accepted.